Neuroendocrine Modulation of Food Intake and Eating Behavior - Iovino, Michele; Messana, Tullio; Lisco, Giuseppe; Mariano, Francesco; Giagulli, Vito A.; Guastamacchia, Edoardo; De Pergola, Giovanni; Triggiani, Vincenzo (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: In the first section of this review, we examined the neuroanatomical and neurochemical data on hunger and satiety centers, glucose receptors, sensorial influences on eating behavior, and regulation of energy requirements. The second section is devoted to orexigenic and anorexigenic hormones. Objective: This paper aimed to overview and summarize data regarding the role of neuroendocrine regulation of food intake and eating behavior. Methods: Appropriate keywords and MeSH terms were identified and searched in MEDLINE/ PubMed. References of original articles and reviews were examined. Results: Hunger and satiety center are located in the lateral (LH) and ventromedial hypothalamus (VMH). Lasting aphagia has been observed following a lesion of LH, while hyperphagia is induced by LH stimulation. On the other hand, increased food intake after VMH lesion and aphagia following VMH stimulation in hungry animals has also been reported. Intracellular glucopenia triggers food intake by reducing neuronal activity at the satiety center level. Moreover, sensory influences are regulated by food palatability as the positive hedonic evaluation of food and energy requirement indicates the average amount of food energy needed to balance energy expenditure. Orexigenic and anorexigenic hormones secreted from the gastrointestinal tract and adipose tissue regulate brain areas involved in eating behavior via gastric afferent vagal nerve, circumventricular organ area postrema, or transporter system. Finally, oxytocin (OT) plays a role in reward-related eating by inhibiting sugar intake and decreasing palatable food intake by suppressing the reward circuitry in the brain. Moreover, the anorectic effect of nesfatin-1 is abolished by an OT antagonist.
Keywords: nesfatin-1